Energy autonomous electronic skin - Carlos García Núñez (Nature Portfolio, 2019)
Abstract Energy autonomy is key to the next generation portable and wearable systems for several applications. Among these, the electronic-skin or e-skin is currently a matter of intensive investigations due to its wider applicability in areas, ranging from robotics to digital health, fashion and internet of things (IoT). The high density of multiple types of electronic components (e.g. sensors, actuators, electronics, etc.) required in e-skin, and the need to power them without adding heavy batteries, have fuelled the development of compact flexible energy systems to realize self-powered or energy-autonomous e-skin. The compact and wearable energy systems consisting of energy harvesters, energy storage devices, low-power electronics and efficient/wireless power transfer-based technologies, are expected to revolutionize the market for wearable systems and in particular for e-skin. This paper reviews the development in the field of self-powered e-skin, particularly focussing on the available energy-harvesting technologies, high capacity energy storage devices, and high efficiency power transmission systems. The paper highlights the key challenges, critical design strategies, and most promising materials for the development of an energy-autonomous e-skin for robotics, prosthetics and wearable systems. This paper will complement other reviews on e-skin, which have focussed on the type of sensors and electronics components.